Co-creation of social innovations and new professional institutions: diffusion of therapeutic patient education (TPE) for diabetes in Austria - Windrum, Paul; Schartinger, Doris; Waring, Justin (Taylor & Francis, 2017)
Patient-centred education in diabetes is a radical social innovation that alters the social and medical relationship between patients and medics. This paper discusses the ways in which institutional work conducted by national and international professional associations has shaped development and diffusion of this social innovation within the Austrian health system. The case study contributes to our understanding of social innovation and institutional change in two respects. First, it highlights the need for purposive institutional work in order to disrupt pre-existing institutions and, thereby, ensure the development and diffusion of a social innovation amongst a community of medical practitioners. Second, the case shows the overtly political work, policing, and educating work that professional associations undertook with funding bodies and key policy-makers in order to develop a national programme for diabetes education.